The near-field wave interference of the steadily advancing monohull ships. (1st May 2023) - Ma, Chao; Zhan, Chengsheng; Peng, Shuitao; Wu, Dongwei; Dong, Zaopeng; Fan, Li; Liu, Zuyuan
Abstract: An extension of the Neumann–Michell theory is given here — a more practical and efficient numerical approach is proposed, which only relates with the flow potential (instead of the related derivatives) and the related coefficients do not need to be updated repetitively during the iterative computations. A practical method is subsequently proposed to decompose the ship waves into the local, transverse or divergent wave components. The near-field ship waves along the ship hull and its effects of the wave interference on the wavelength, the wave drag and the hydrodynamic pressure are then considered. Clear relations between the near-field wavelength of the transverse or divergent ship waves and the Froude number are found, and the unfavorable or favorable interference relations in the near-field are given, which can predict the peaks or valleys of the wave drag more reasonable than the traditional far-field wave interference relations. Moreover, the effects of the transverse wave interference in the near-field is found more important than it conventionally believed, and it could be partially cancelled out by the wave interference of the divergent ship waves around the ship hull. Highlights: The Neumann–Michell theory is extended here to be more efficient. The ship waves is decomposed into the local, transverse or divergent wave components. Clear relations between the near-field wavelength and the Froude number are found. The wave interference relations in the near-field are subsequently researched.